Representasi Psikoanalisis Sigmund Freud Dalam Film “Nanti Kita Cerita Tentang Hari Ini” Karya Marcella F. P. - Audrina Syafa Pratiwi; Yuniseffendri (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This study aims to describe the representation of Sigmund Freud’s psychoanalysis in the film Nanti Kita Cerita Tentang Hari Ini by Marcella F. P., focusing on personality structure, defense mechanisms, and unconscious motivation of the main characters. This research employs a descriptive qualitative method within a literary psychology approach. The data consist of dialogues, scenes, and characters’ actions collected through visual observation, documentation, and literature review. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results reveal that the characters’ personality structures consist of id, ego, and superego, which interact dynamically in shaping behavior. The id appears through spontaneous emotional impulses, the ego functions as a mediator that considers reality, and the superego reflects the internalization of family moral values. Furthermore, various defense mechanisms such as repression, rationalization, and projection are identified as strategies used by the characters to reduce anxiety caused by intrapsychic conflicts. Unconscious motivation also plays a significant role in influencing behavior, particularly related to past trauma, repressed desires, and inner conflicts within family relationships. Therefore, this study demonstrates that film serves not only as entertainment media but also as a representation of complex psychological dynamics within individuals in a family context.